Physical load exposure at construction sites - Hartmann, Bernd; Fleischer, Andreas G. (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'This field study analyzed work-related causes of musculoskeletal disorders to investigate the structure of physical workload in different occupations in the construction industry and rank different tasks with respect to the load on the lumber spine. ' ' METHODS ': 'An observation instrument (Arbeitswissenschaftliches Erhebungsverfahren für Bauarbeiten) and a specially devised data retrieval system (Allgemeines Datenerfassungs- und Analysesystem für Bauarbeit) provided material for a large database which allowed a differentiated analysis of load exposures. The study was comprised of data from 340 construction workers (bricklayers, scaffolders, carpenters, plumbers, and painters). On the basis of a regular daily worktime of 8 hours, specific statistical aspects were studied concerning manual materials handling, biomechanical pressure on lumbar disc L5/S1, and posture constraints during kneeling, squatting, bending and overhead positions. ' ' RESULTS ': 'The scaffolders (13.7% of the regular daily worktime), bricklayers using bricks requiring two hands (7.1%), and carpenters (6.7%) handled weights of >10 kg. With respect to lumbar disc L5/S1, the scaffolders and bricklayers often showed pressures in excess of 3.4 kN. Bricklaying required bent postures for 20.7–35.6% of the daily worktime. The painters (23.8%), plumbers (16.7%), and carpenters (7.2%) often worked in kneeling postures. The painters often used overhead positions (18.3%). The bricklayers and scaffolders had high frequencies of materials handling. The recovery time for this repetitive work was longer than threefold the load time. ' ' CONCLUSIONS ': 'This study showed that it is possible to rank different construction tasks with respect to load exposure. In addition it was shown that preventive measures such as improved ergonomic design, organizational structure, training, and medical health care are needed.
Keywords: construction site; construction worker; field study; lumbar spine pressure; MSD; musculoskeletal disorder; physical load exposure; posture constraint; repetitive manual materials handling